Toxicity of Agave sisalana extracts on Cordyceps and their effect and the association with fungi on Nasutitermes corniger (Isoptera: Termitidae) - da Silva Lopes, Rosineide; Barroso Martins, Mônica Cristina; De Lima, Geiziquele; Gonçalves de Oliveira, Luciana; Félix da Costa, Antonio; Dos Santos, Venézio Felipe; Dos Santos Correia, Maria Tereza; Da Silva, Nicácio Henrique; Correia de Albuquerque, Auristela; Áurea de Luna Alves Lima, Elza; De Menezes Lima, Vera Lúcia (Revista Colombiana de Entomología, 2022)
Nasutitermes corniger is an arboreal termite that causes economic damage in urban areas, and its control is for chemical insecticides. An alternative for insect control is the use of entomopathogenic fungi and plant extracts, or the synergistic effect of the association of these. The toxicity of aqueous and hydroethanolic extracts of Agave sisalana on the biological aspects of the fungal Cordyceps farinosa, C. fumosorosea and C. javanica and the action of the extracts and their synergistic effect on N. corniger was examined. The effect of the extracts on fungi was evaluated by germination, sporulation and mycelial growth of fungi in Sabouraud medium through the study of biological aspects under laboratory conditions; and control of N. corniger were examined, by ingestion of extracts and of the association extract plus fungus on filter paper, being the percentage of mortality of soldiers and workers of the termite daily. In general, the extracts were inoffensive to the fungi at concentrations 10, 25, 50, 100 and 200 mg.mL-1. The extracts demonstrated termiticidal actions at concentrations tested, causing the mortalities about 100% of the workers after the third and sixth days (LC50: 0.778 to 0.803 mg.mL-1) and 100% of the soldiers between the fourth and seventh days (LC50:0.146 to 0.956 mg.mL-1). The association of the extracts with C. farinosa ESALQ1355 was more efficient in inducing the mortality in N. corniger. These results demonstrated the efficiency in vitro of the sisal extracts in controlling N. corniger termites, alone or in combination with fungi, suggesting their potential joint usefulness in the biological control of insect pests.